The utility of muscle magnetic resonance imaging in idiopathic inflammatory myopathies: a scoping review - Paik, Julie J.; Christopher-Stine, Lisa; Boesen, Mikael; Carrino, John A.; Eggleton, S. Peter; Denis, Deborah; Kubassova, Olga (Frontiers in Immunology, 2025)
Idiopathic inflammatory myopathies (IIMs) are muscle disorders characterized by proximal weakness of the skeletal muscles, inflammation in muscle, and autoimmunity. The classic subgroups in IIMs include dermatomyositis, inclusion body myositis, immune-mediated necrotizing myopathy, and polymyositis (PM). PM is increasingly recognized as a rare subtype and often included in overlap myositis, the antisynthetase syndrome when no rash is present, or misdiagnosed inclusion body myositis. Magnetic resonance imaging (MRI) has played an increasingly important role in IIM diagnosis and assessment. Although conventional MRI provides qualitative information that is helpful for diagnosis, its application for the quantitative assessment of disease activity is challenging. Therefore, advanced quantitative MRI techniques have been implemented in the past 10 years to highlight potential new applications of disease monitoring in IIM. The aim of this review is to examine the role of quantitative MRI techniques in evaluating the key imaging features of IIM, mainly muscle edema and muscle damage (fatty replacement and/or muscle atrophy).